Cyberbullying: a comparative analysis between the results of a scoping study and a questionnaire applied to students - Coutinho, Luís; Lencastre, José Alberto; Tomás, Ana Maria (Frontiers in Computer Science, 2025)
This article presents a scoping study using the Scopus Database to analyze literature on cyberbullying and students’ perceptions. Using the keywords ‘cyberbullying’, ‘students’, and ‘perceptions’, we narrowed down 6,271 initial articles to 14 that met our inclusion criteria. Additionally, we conducted a questionnaire survey with 193 Portuguese students aged between 10 and 19 to understand their perceptions of cyberbullying. Our analysis revealed cyberbullying as a growing concern with significant negative impacts on students’ mental and emotional wellbeing. The correlation between our questionnaire results and the scoping study findings emphasizes the urgent need for comprehensive intervention strategies. Our research indicates that effective cyberbullying prevention requires a multi-faceted approach including: development of social and emotional skills among students; promotion of appropriate technology use beyond technical literacy; targeted teacher training programs; establishment of clear intervention protocols within schools; empowerment of cyber-observers as active prevention agents; and recognition that cyberbullying often functions as an extension of face-to-face aggression rather than anonymous attacks. This study brings into focus the critical importance of fostering digital citizenship within educational settings, with teachers and school administrators playing pivotal roles in creating safe digital environments. The findings underscore how properly structured educational interventions can significantly increase reporting rates and decrease cyberbullying incidents, thereby promoting students’ overall wellbeing in the digital age.